2021
DOI: 10.1111/1754-9485.13149
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced ultrasound after successful cryoablation of benign and malignant renal tumours: how long does tumour enhancement persist?

Abstract: Introduction: To investigate how long successfully ablated tumours take to become completely avascular at CEUS after cryoablation. Methods: Ninety-five patients had percutaneous cryoablation of 103 renal tumours investigated at CEUS on post-operative day one. If the lesion was avascular, a contrast-CT/MR was scheduled six months after the procedure, while CEUS was repeated if the lesion still displayed enhancement, until the disappearance of intralesional vascularity. Technical success was defined when the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…In accordance with the EAU guidelines [28], evaluation of ablative treatments of small kidney lesions requires a close monitoring of the ablated area, both to check for any complications and to assess the success of the procedure. CEUS has progressively taken a role in the follow-up, especially early after the procedure [29][30][31]. The treatment is considered successful if the lesion becomes completely avascular.…”
Section: Follow-up Of Tumor Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the EAU guidelines [28], evaluation of ablative treatments of small kidney lesions requires a close monitoring of the ablated area, both to check for any complications and to assess the success of the procedure. CEUS has progressively taken a role in the follow-up, especially early after the procedure [29][30][31]. The treatment is considered successful if the lesion becomes completely avascular.…”
Section: Follow-up Of Tumor Ablationmentioning
confidence: 99%
“…The treatment is considered successful if the lesion becomes completely avascular. This usually occurs early after radiofrequency and microwave ablation (Figure 5) [29,32], while it may take up to one month after cryoablation (Figure 6), requiring a tailored follow-up [30,31]. Therefore, an adequate knowledge of the type of ablative treatment allows a correct interpretation of the images, thus reducing the risk of misdiagnosis.…”
Section: Follow-up Of Tumor Ablationmentioning
confidence: 99%
“…Additionally, the lack of a biopsy of the ablated area is a limitation of our study, considering that it could have ruled out false positive recurrences. The enhancement persistence in the ablated area can last for over a month after the procedure [30], and the lack of evidence on this topic make the management of these patients challenging.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 CEUS has been applied in a range of ablative modalities, including microwave ablation, alcohol ablation, radiofrequency ablation, cryoablation, and irreversible electroporation. 20 21 Solbiati et al demonstrated much lower partial ablation rates using CEUS than conventional means (16.1% vs. 5.9%). 22…”
Section: Methodsmentioning
confidence: 99%